Incorporating community education in the strategy for harpy eagle conservation in Panama (2022)
eng:Many species of top predators are threatened, in large part, because of human destruction. Although conservation programs that include captive breeding, release, and research are vital, environmental education is just as important for the long-term survival of many wildlife species. In Panama, The Peregrine Fund developed an education program to support the restoration of threatened Harpy Eagle populations. The authors identified why people kill this species, and they created an education program to mitigate the annihilation of Harpy Eagles. Using teacher training workshops, mass media, and a unique scientific and cultural knowledge exchange, coupled with adaptive management evaluation methods, this program has been able to stem the tide of human destruction of this species in the Panama Canal Watershed area.